2017
DOI: 10.1044/2017_ajslp-16-0129
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Negative Evaluation, Trait Anxiety, and Judgment Bias in Adults who Stutter

Abstract: Judgment bias in PWS is mediated by the magnitude of FNE present; not all PWS exhibit judgment bias for social situations. Treatment implications include the need for psychosocial support addressing the negative impacts on quality of life and restrictions on social engagement that stuttering may cause in some individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…One related previous study investigated the relationship between fear of negative evaluation (a core component of social phobia) and judgment bias (another form of cognitive bias) among adults who do and do not stutter (Brundage et al, 2017).…”
Section: Social Anxiety Influenced Interpretations For Both Groupsmentioning
confidence: 99%
“…One related previous study investigated the relationship between fear of negative evaluation (a core component of social phobia) and judgment bias (another form of cognitive bias) among adults who do and do not stutter (Brundage et al, 2017).…”
Section: Social Anxiety Influenced Interpretations For Both Groupsmentioning
confidence: 99%
“…In several studies, it has been shown that AWSs scores on the Fear of Negative Evaluation (FNE) and Social Avoidance and Distress (SAD) were higher than control groups. [ 8 9 10 ] Based on the relationship between social anxiety symptoms and stuttering, it was suggested that anxiety reduction strategies should be considered as another focus of stuttering treatment along with speech therapy (ST). [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…This study is the first empirical investigation of interpretation bias and stuttering. One related previous study investigated the relationship between fear of negative evaluation (FNE; a core component of social phobia) and judgment bias (another form of cognitive bias) among adults who do and do not stutter (Brundage et al, 2017). Although the adults who stutter in that study reported higher degrees of FNE than the non-stuttering adults, both groups perceived threat in ambiguous scenarios comparably.…”
Section: Social Anxiety Influenced Interpretations For Both Groupsmentioning
confidence: 86%
“…In a more naturalistic context of giving an oral presenation, adults who stutter have shown to look more at negative and neutral audience members than at positive ones (Lowe et al, 2012), although this selective attention towards negative faces did not appear in the results of that research group's dot-probe task (Lowe et al, 2016). In a more explicit bias task measuring judgement bias, fear of negative evaluation (a central component of social anxiety) mediated the degree of perceived social threat among adults who stutter (Brundage, Winters, & Beilby, 2017). This collection of preliminary evidence suggests a promising link between stuttering, cognitive bias, and social anxiety, although the majority of this burgeoning line of work has related to adults who stutter.…”
Section: Chapter 1: Introductionmentioning
confidence: 85%
See 1 more Smart Citation